Development of a CD-ROM based learning courseware for physics form 4, chapter 5 light by using tutorial strategy [electronic resource] - 278581 Siow, Ching Yen (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Sains dan Komputer serta Pendidikan (Fizik)) - Universiti Teknologi Malaysia, 2008